The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/healthcare9101400
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Colorectal Polyps Based on Cardiorespiratory Fitness, Muscle Strength, Health Behavior, and Abdominal Obesity in Asymptomatic Elderly

Abstract: Colorectal polyps are precursor lesions of colorectal cancer and are known to be associated with obesity, low physical activity, and unhealthy behavior. This cross-sectional study analyzed the prevalence of colorectal polyps based on cardiorespiratory fitness (CRF), muscle strength, and health behavior in older adults. Participants were asymptomatic and included 1024 men and 472 women aged 65–80 years who visited the health care center. Colonoscopy was performed under conscious sedation, and cardiorespiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
1
4
0
1
Order By: Relevance
“…53,54 The mechanism of this effect is unknown, but it can lead to decreased insulin levels, systemic inflammation, and abdominal obesity. 53,55 Finally, similar to other studies, [56][57][58] we indicated that patients with a positive family history of diverticulitis are at higher risk for diverticulitis. This phenomenon might be explained by the fact that some genes, such as LAMB4, TNFSF15, ARHGAP15, ANO1, ELN, and SPINT2, play known roles in processes logically related to diverticulitis, including inflammation, intestinal transport, intestinal motility, and extracellular matrix formation.…”
Section: Number Of Diverticulasupporting
confidence: 88%
“…53,54 The mechanism of this effect is unknown, but it can lead to decreased insulin levels, systemic inflammation, and abdominal obesity. 53,55 Finally, similar to other studies, [56][57][58] we indicated that patients with a positive family history of diverticulitis are at higher risk for diverticulitis. This phenomenon might be explained by the fact that some genes, such as LAMB4, TNFSF15, ARHGAP15, ANO1, ELN, and SPINT2, play known roles in processes logically related to diverticulitis, including inflammation, intestinal transport, intestinal motility, and extracellular matrix formation.…”
Section: Number Of Diverticulasupporting
confidence: 88%
“…Current data collectively demonstrated that patients with MAFLD who had concomitant obesity or central obesity had a 1.28- or 6.00-fold significantly increased risk of colorectal adenoma, respectively. Similarly, Zhang S et al reported that obesity, especially central obesity, increases the incidence of colorectal polyps and that central obesity is independently associated with the development of adenomatous polyps [ 39 ]. Moreover, increased BMI has been found to increase the risk of CRC [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Посредством колоноскопия се открива заболяемост от колоректални полипи от 65,2% сред 1024-ма мъже и от 48,5% сред 472 жени на възраст между 65 и 80 г. (23). Отношението на шансовете спрямо затлъстяването е 1,151 (между 1,010 и 2,291 при доверителен интервал от 95%) при мъжете и 1,178 (между 1,015 и 2,612 при доверителен интервал от 95%) при жените.…”
Section: обсъжданеunclassified